Strategies in Translating Idiomatic Expressions Found in Dave Pelzer's Novel A Child Called 'IT' Into A Child Called 'IT' by Danan Priatmoko - Lilik Sugiarti; Thathit Andini (University of Muhammadiyah Malang, 2015)
Strategies in Translating Idiomatic Expressions Found in Dave Pelzer's Novel A Child Called 'IT' Into A Child Called 'IT' by Danan Priatmoko